A Successful Treatment of Ostraceous Psoriasis Associated with Psoriatic Arthritis in Children: A Case Report - Rowawi R; Dwipangestu G; Suwarsa O; Dharmadji HP; Sutedja E; Pangastuti M; Gunawan H (Dove Medical Press, 2020)
Rasmia Rowawi, Gilang Dwipangestu, Oki Suwarsa, Hartati Purbo Dharmadji, Endang Sutedja, Miranti Pangastuti, Hendra Gunawan Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin Hospital, Bandung 40161, IndonesiaCorrespondence: Hendra GunawanDepartment of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin General Hospital, Jl.Pasteur No. 38, Bandung, West Java 40161, IndonesiaTel/Fax +62 22 2032426 ext. 3449Email h.gunawan2016@unpad.ac.idAbstract: Psoriasis may manifest as severe hyperkeratotic lesions resembling an oyster shell called ostraceous psoriasis (OP). This type of psoriasis is extremely rare and is often associated with psoriatic arthritis (PA). Cases of OP associated with PA in children have never been reported before. We reported a 9-year-old girl with hyperkeratotic lesions resembling an oyster shell all over the body accompanied with swelling on joints of both fingers, knee joints, and ankle. Histopathological examination supported the diagnosis of OP. The diagnosis of PA was established according to the Classification Criteria for Psoriatic Arthritis (CASPAR). Significant improvements of the skin lesions and joints involved were observed within 44 days after the beginning of treatment with cyclosporine and a combination of high potent topical steroid with emollient. OP associated with PA is uncommonly seen in children. High potent corticosteroid combined with emollient showed good result in skin improvement with low side effects. In addition, cyclosporine can be a good choice of systemic therapy for OP with PA in children.Keywords: children, corticosteroid, cyclosporine, ostraceous psoriasis, psoriatic arthritis